Parental Leave and Intimate Partner Violence - Dan Anderberg; Line Hjorth Andersen; N. Meltem Daysal; Mette Ejrnæs (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We study the effects of a parental leave reform in Denmark in 2002 on intimate partner violence (IPV) contacts. The reform extended leave-taking among mothers but not fathers and led to a marked reduction in IPV incidence, specifically among mothers with below-median years of education. Analysis of further outcomes suggests that increased birth spacing is a key mechanism linking extended parental leave to reduced IPV risk.
Keywords: J12; I38; 330; intimate partner violence; parental leave